2019
DOI: 10.3988/jcn.2019.15.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Levels of β-Amyloid 40 and β-Amyloid 42 are Proportionately Decreased in Amyloid Positron-Emission Tomography Negative Idiopathic Normal-Pressure Hydrocephalus Patients

Abstract: Background and Purpose Cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) could be misleading in idiopathic normal-pressure hydrocephalus (iNPH). We therefore investigated the CSF biomarkers in 18F-florbetaben amyloid-negative positron-emission tomography (PET) [amyloid PET(−)] iNPH, amyloid-positive PET [amyloid PET(+)] AD, and cognitively normal (CN) subjects. Methods Ten amyloid PET(+) AD patients (56.7±5.6 years old, mean±standard deviation), 10 amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…In fact, recent studies showed that CSF Aβ42 levels can be decreased in pure NPH. 23 24 25 We compared our cutoffs with previously established cutoffs obtained from other memory clinics in Korea. As a result, our Aβ42 cutoff was comparable with Jung et al's (Aβ42 < 631.8, p-tau > 56.4, and t-tau > 271.6) and our t-tau cutoff was comparable with Park et al's (Aβ42 < 481.8, p-tau > 57.0, and t-tau > 326.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, recent studies showed that CSF Aβ42 levels can be decreased in pure NPH. 23 24 25 We compared our cutoffs with previously established cutoffs obtained from other memory clinics in Korea. As a result, our Aβ42 cutoff was comparable with Jung et al's (Aβ42 < 631.8, p-tau > 56.4, and t-tau > 271.6) and our t-tau cutoff was comparable with Park et al's (Aβ42 < 481.8, p-tau > 57.0, and t-tau > 326.0).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that there are other conditions causing false positive CSF Aβ42 and t-tau results: CSF Aβ42 is reported to be decreased, albeit inconsistently, in frontotemporal dementia, vascular dementia, dementia of Lewy body, 30 or in normal pressure hydrocephalus. 31 CSF t-tau, which is a neuronal injury marker, can increase in various brain disorders such as stroke, trauma, and non-AD dementias, especially in rapidly progressing dementias such as Creutzfeldt-Jakob Disease.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the study by Wilsson et al [14], CSF t -tau, p -tau 181 , and Aβ 42 levels were all significantly lower than controls. In the study using amyloid PET, Kim et al [15] revealed Aβ 42 levels were decreased in iNPH and AD patients and more in AD. In our cohort, t -tau and p -tau 181 level of iNPH was not distinguishable from control and significantly lower than AD.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the abnormal CSF dynamic and turnover as well as reduced glymphatic system clearance of Aβ in iNPH patients also contributed to the amyloid mismetabolism [18]. The proportionate decrease of Aβ 42 and Aβ 40 in CSF of iNPH but not in AD also suggested there were discrete amyloid clearance and pathology in these 2 diseases [15, 19]. p -tau 181 was related to the formation of neurofibrillary tangles in AD, which was not detected in iNPH.…”
Section: Discussionmentioning
confidence: 99%
“…These changes have been known to play a part in decreasing the pattern of learning and memory processes and impairing cognitive properties ( Hartman and Ross, 2018 ). In cerebrospinal fluid (CSF), a disproportion of Aβ to Aβ42 protein is a key criterion to confirm the pathology of AD clinically ( Kim et al, 2019 ). Even though the symptoms of diverse neurodegenerative dementias are often similar, each is usually distinguished by the deposition of its characteristic protein isoform in specific brain areas.…”
Section: Introductionmentioning
confidence: 99%